2016
DOI: 10.1080/0167482x.2016.1265500
|View full text |Cite
|
Sign up to set email alerts
|

A study of sociocultural factors on depression in Chinese infertile women from Hunan Province

Abstract: Sociocultural factors influence depression levels in Chinese female infertile patients. The unique aspects of Chinese culture may have a negative mental impact on the patients, and cultural factors should be taken into consideration in the development of coping strategies for Chinese infertile women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…A meta-analysis by Frederiksen et al [50] indicated that psychological interventions for reducing depression among infertile women would result in the greater success of infertility treatments and higher rates of pregnancy. Depression is assumed as a negative influence on mental health and, consequently, physical and social health [51]. The provision of supportive services and psychological counseling intended to help women manage and cope with infertility would effectively minimize the prevalence of depression among this group [52].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Frederiksen et al [50] indicated that psychological interventions for reducing depression among infertile women would result in the greater success of infertility treatments and higher rates of pregnancy. Depression is assumed as a negative influence on mental health and, consequently, physical and social health [51]. The provision of supportive services and psychological counseling intended to help women manage and cope with infertility would effectively minimize the prevalence of depression among this group [52].…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were measured by the Chinese version of the Zung Self‐Rating Depression Scale. Score ≥ 50 was used to define depressive symptoms . Television (TV) viewing time was estimated by asking: “How many hours a day do you usually spend watching TV?”.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization predicted that infertility would be the third largest disease of the twenty-first century, after tumors and cardiovascular disease (Li et al, 2016). Infertility has been estimated to affect as many as 186 million people worldwide, most of whom are residents of low-resource countries (Inhorn & Patrizio, 2015;Ombelet & Campo, 2007).…”
Section: Introductionmentioning
confidence: 99%